The New-Normal of Talent & Knowledge Management – A Framework towards Virtual Learning – Post- COVID-19 - Vidya S. Patil; Supratim Chowdhury, CMT. (International Journal of Engineering and Management Research, 2020)
Indian economy since the pre and post-independence period has witnessed a drastic transformation from an agrarian economy to a knowledge-based economy thus creating a knowledge-based workforce and organisations. With the change of time, the learning became more complex and necessity thus creating havoc and high-pace change in the character of the job in an organisation even creating a situation where artificial intelligence is replacing human intelligence. Today’s employees are more competitive in terms of skills, pay-packages, and also work challenges. Amidst of all these changes, the present uncertainty and crisis hovering the entire world i.e .the Corona Virus pandemic which has forced almost all organizations to accept virtual learning and virtual knowledge sharing as a competitive edge and adapting virtual-cost-effective learning and communication system. It is prime time when the management of the organisation has to initiate a holistic approach towards virtual learning and knowledge sharing with a clear objective of up-skilling its workforce to new normals during and post-pandemic. The new normal norms will bring in new challenges of a new set of skills and competencies and operational processes to revive the broken economy and business setbacks. This paper further concentrates and focuses on applying and improving virtual knowledge management practices in organisation. It also focuses on effective talent up-gradation and management systems which most important in the present scenario to have a ‘Fact-Based Communication' And 'Virtual Connectivity'. Here, Descriptive Research is adopted for the study. Literature review of articles and research papers is analytically conducted to develop a significant process for crucial talent management systems that will aid in the up-skilling workforce through virtual mode to combat and resurgence the Post- COVID-19.